A "one-step" approach to the highly efficient synthesis of lactide through the confinement catalysis of covalent organic frameworks. Issue 8 (3rd April 2023) - Zhao, Jinyu; Guo, Guangming; Wang, Danbo; Liu, Hui; Zhang, Zhenxiu; Sun, Lishui; Ding, Naixiu; Li, Zhibo; Zhao, Yingjie
Abstract : The precision confinement effect of the highly ordered channels with functional moieties in the designed 2D COFs realizes the highly efficient conversion from the lactide acid to the cyclic dimer lactide directly and avoids oligomerization. Abstract : The efficient synthesis of lactide with high purity is the key to poly-lactic acid (PLA) production. Here, we demonstrated a 2D COFs-based catalyst, which could convert l -lactic acid into l -lactide directly in an excellent yield (80%) under mild conditions. Similar to enzymatic catalysis in which the product selectivity is controlled by the enzyme pocket, the precision confinement effect of the highly ordered channels and adjustable structures with functional moieties of the COFs play key roles in converting the monomer to the cyclic dimer directly and avoiding oligomerization. This strategy is sharply different from the current two-stage process for synthesizing lactide. The reactions are carried out at a lower temperature and under atmospheric pressure, which reduces the energy consumption significantly. In addition, this newly developed method avoids the use of metal catalysts and meets the demands of the environmental friendly trend in chemical synthesis. Last, the functions of the emerging COFs materials as excellent heterogeneous catalysts with a confinement effect were further explored.